Cordes–Nirenberg type estimates for nonlocal parabolic equations. (January 2016) - Kim, Yong-Cheol; Lee, Ki-Ahm
Abstract: In this paper, we obtain Cordes–Nirenberg type estimates for nonlocal parabolic equations on the more flexible solution space L T ∞ ( L ω 1 ) than the classical solution space B ( R T n ) consisting of all bounded functions on R T n .